Mapping Research on Profitability Ratios in Islamic Banking: A Bibliometric Study Using VOSViewer and Literature Review - Reza Rahmad Marpaung; Rahmaniyah Indriaputri (JEBMAFA: Journal of Economics, Business, Management, Accounting, Finance, and Administration, 2025)
This study aims to map research trends and identify gaps related to profitability ratios in Islamic banking, as well as to analyze the influence of internal factors, risk management, and external conditions on bank profitability. A mixed-methods approach was employed, combining bibliometric analysis using VOSviewer and a literature review of Sinta-accredited national journals from 2015–2024. Bibliometric analysis was conducted to visualize publication networks, categorize thematic clusters, and highlight frequently and underexplored research topics. The literature review examined the relationships between internal efficiency, risk management, and external factors with profitability. The results indicate that Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) are the primary profitability indicators, closely associated with internal efficiency (BOPO, NIM), risk management (Non-Performing Financing, Financing to Deposit Ratio, Capital Adequacy Ratio), and external factors such as regulations and macroeconomic conditions. Cost efficiency, margin management, and effective risk control are key drivers of sustainable profitability. This study is expected to serve as a reference for future research on the comprehensive determinants of bank profitability.